Development of Flip PDF And Video Based E-Modules to Improve Mathematics Learning Outcomes - Helti Lygia Mampouw; Yogani Indah Pawestri; Tri Nova Hasti Yunianta (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The decline in national exam results for junior high school students in 2017-2019 decreased yearly, with achievement in 2019 of 46.46%, with the lowest mathematics score compared to other subjects. This research aims to produce a valid, practical, and efficient. E-module is used to create an E-module system of linear equations in two variables that meet applicable criteria. This study uses Research and Development (R&D) research using the ADDIE method, namely analysis, design, development, implementation, and evaluation; researchers develop E-modules, a system of linear equations in two variables accessed via the internet. E-modules that are created apply concepts in daily life or contextually so students can easily understand The tool used in the module is Flip pdf edition corporate. The participants of this study were 34 class VIII students of SMP N 1 Suruh for the 2021/2022 academic year. The development of the E-module system of linear equations in two variables gets a good response from students by getting an average of 88% in the excellent category, practicality average is 87,5% in the excellent category, so this E-module is feasible to use in the learning process, the resulting impact students can understand the material with interest and curiosity to learn. The use of E-modules must pay attention to the weaknesses of students who need the facilities and infrastructure to access the media E-module.